Fungal Gummosis in Peach - Daniel Mancero-Castillo; Ali Sarkhosh; Sara Sherman; Mercy Olmstead; Philip Harmon; Thomas Beckman (EDIS, 2018)
Peach fungal gummosis (PFG) is a vascular disease that limits the growth and yield of peach orchards in the southeastern United States. This 6-page document discusses the symptoms and management of PFG. Written by Daniel Mancero-Castillo, Ali Sarkhosh, Sara Sherman, Mercy Olmstead, Philip Harmon, and Thomas Beckham and published by the UF/IFAS Horticultural Sciences Department, July 2018. https://edis.ifas.ufl.edu/hs1265